Comparison of IgG antibody profiles by immunoblotting in patients with acute and previous Toxoplasma gondii infection. Issue 7 (July 1991) - Moir, I L; Davidson, M M; Ho-Yen, D O
Abstract : The IgG antibody profile to Toxoplasma gondii proteins of less than 37 kilodaltons in sera from patients with acute and previous infection was studied by immunoblotting. Bands at 28, 29, and 36 kilodaltons were more common in acute infection (10 out of 10, nine out of 10, and nine out of 10, respectively) compared with previous infection (five out of 10, four out of 10, and one out of 10, respectively). The 6 kilodalton band was present in 10 out of 10 sera from patients with acute infection and five out of 10 sera from those with previous infection. A new observation is a doublet of bands of 22-25 kilodaltons present only in sera from patients with acute infection. This doublet may be a more reliable indicator of acute infection than the 6 kilodalton band.